Education and Socialization of Students Physical Fitness Assessment in Vocational High Schools in Singkawang City - Stephani Yane; Iskandar; Heri Rustanto; Awang Roni Effendi; Rio Wardhani (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
The purpose of this community service activity is to provide education and an introduction to physical fitness for students at State Vocational High School 3 Singkawang, particularly in measuring students physical fitness levels. Based on field data, many Physical Education (PJOK) teachers still have limited understanding of the National Sports Grand Design (DBON). In addition, students have never received assessments of their physical fitness, which results in decreased concentration during PJOK learning activities and rapid fatigue during physical activities. The method applied is service learning, in which students receive education and understanding of the importance of physical fitness through collaboration with PJOK teachers at the school. The stages include: (1) completion of questionnaires/pre-tests, (2) socialization and measurement of students physical fitness, (3) completion of questionnaires/post-tests, and (4) activity documentation. The implementation of this community service program received positive responses, as reported by the PKM team, including: (1) enhanced understanding of measuring physical fitness through the Indonesian Student Fitness Test (TKPN), and (2) best practices in the field for measuring physical fitness using the Indonesian Student Fitness Test (TKPN)